2015
DOI: 10.1188/15.onf.165-173
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practice Beliefs and Behaviors 
of Nurses Providing Cancer Pain Management: 
A Mixed-Methods Approach

Abstract: Purpose/Objectives To describe evidence-based practice (EBP) beliefs and behaviors of nurses who provide cancer pain management. Design Descriptive, cross-sectional with a mixed-methods approach. Setting Two inpatient oncology units in the Pacific Northwest. Sample 40 RNs. Methods Data collected by interviews and web-based surveys. Main Research Variables EBP beliefs, EBP implementation, evidence-based pain management. Findings Nurses agreed with the positive aspects of EBP and their implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
1
22
1
Order By: Relevance
“…institutions have managed to bolster the confidence of nurses to provide the best care to oncological patients after going through EBP educational programs (45) .…”
Section: Discussionmentioning
confidence: 99%
“…institutions have managed to bolster the confidence of nurses to provide the best care to oncological patients after going through EBP educational programs (45) .…”
Section: Discussionmentioning
confidence: 99%
“…A significant individual barrier to EBP is the knowledge and skills of the clinician to translate evidence into practice. Students in this study, consistent with nurses in general, entered the curriculum with strong EBP‐B (Eaton et al., ; Johansson, Fogelberg, Dahm, & Wadensten, ; Melnyk, Fineout‐Overholt, Gallagher‐Ford, & Kaplan, ; Underhill et al., ). Faculty EBP mentors were able to provide an environment or culture of EBP within a supportive educational setting.…”
Section: Discussionmentioning
confidence: 61%
“…Students’ EBP knowledge and skills were strengthened across the curriculum and they reported significant gains in EBP‐B after completing the curriculum. Research has shown that although nurses have positive EBP beliefs, there are many barriers that impede them in turning beliefs into action though EBP implementation (Balas & Boren, ; Eaton et al., ; Melnyk, Fineout‐Overholt, Gallagher‐Ford, & Kaplan, ; Sadeghi‐Bazargani et al., ; Ubbink et al., ; Underhill et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current column reviews an article about the evidence-based-practice beliefs and behaviors of the nurses concerning cancer pain management. Eaton et al (2015) reported the evidence-based practice beliefs and behaviors of nurses providing cancer pain management in the U.S. The purpose of the study was to describe antecedents to evidence-based pain management decision-making of nurses who provide care to patients with cancer pain and explore if any significant relationships exist between nurses' characteristics and their antecedents to evidence-based pain management decision-making.…”
mentioning
confidence: 99%